(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The authors analyzed phitosystems morphology in geologic nature monument «Slantsevi Skeli» based on a full description of vegetation components. The analysis revealed the domination of xeromorphic herbs and turf grasses in vegetation. It also allowed to indicate synmorphotypes of plant communities and described their most common forms. This article presents varieties of synmorphological vegetation groups and their schematic graphics. Typical for this area synmorphotypes of plant communities were differentiated and selected. It should be noted that the differentiation of vegetation synmorphotypes determined by ecotopic conditions.